Digital Communication in the Formation of Teen Character: An Analysis of the Facebook Account 'Amperaku' in Ampera Village - Ibrahim, Almunawar; Muhammad, Burhanudin A.; Hasim, Iksan; Jailan, Putri Nurdiana (International Journal of Education, Information Technology, and Others, 2025)
This study aims to analyze digital communication on the character formation of adolescents in Ampera Village and identify social and moral values that develop through digital interactions. The research method used is qualitative with a descriptive type/approach, aiming to analyze digital communication on the character formation of adolescents in Ampera Village and identify social and moral values that develop through digital interactions. This study found that digital communication in the Facebook account "Amperaku" shapes the character of adolescents in Ampera Village, providing an illustration that Ampera Village adolescents interact with each other using symbolic like and super emoticons to respond to posts on the Facebook account "Amperaku", and share posts on their respective accounts as a form of support from among the village's adolescents. In addition, the existence of the Facebook account "Amperaku" has a huge impact on personal and social thought patterns and actions.